Performance Evaluation of the Operating Rooms in the Largest Teaching Hospital in South of Iran, before and after Implementation of the Health Care Reform Plan - Payvand Bastani; Zahra Kavosi; Mahdieh Sadat Ahmadzadeh; Zohreh Rezaee (Kerman University of Medical Sciences, 2016)
Introduction: Surgical ward is one of the main wards of each hospital that its efficiency is a leading factor in determining the hospital costs. Health care reform plan has been implemented to increase the public satisfaction with health care system and reduce the hospital costs. The aim of this study was to evaluate performance of the operating rooms, before and after implementation of the health care reform plan. Methods: In this descriptive-analytical study, the extracted information from hospital records of all patients (64370 cases) who had undergone surgery from July 2013 to March 2015, were recorded in a researcher-made checklist. Data were statistically analyzed using paired t-test by SPSS 19. Results: The average number of surgical procedures performed in all wards of the teaching hospital was increased after implementation of the health care reform plan. There was also statistically significant difference between all the inpatient surgeries and all the scheduled and unscheduled ones (P<0.05). Conclusion: Health care reform plan had a significant effect on supply and demands for services in the teaching hospital that can be due to financing through the plan that increased the demand for surgical service delivery. Keywords: Operating Room, Surgical Procedures, Teaching Hospital, Health Care Reform Plan Citation: Bastani P, Kavosi Z, Ahmadzadeh M, Rezaee Z. Performance Evaluation of the Operating Rooms in the Largest Teaching Hospital in South of Iran, before and after Implementation of the Health Care Reform Plan. Journal of Health Based Research 2016; 2(2): 197-205.